A meta-analysis on the effects of incarceration-based opioid substitution treatment. (January 2023) - Boksán, K.; Dechant, M.; Weiss, M.; Hellwig, A.; Stemmler, M.
Objective: Opioid substitution treatment (OST) is a common treatment for individuals who use opioids; however, empirical evidence on the effects of OST during incarceration is scarce. Our aim was to conduct a meta-analysis on the effects of incarceration-based OST on substance use, treatment engagement post-release and re-incarceration.Method: We searched for studies on individuals who were incarcerated and treated with OST, compared to a comparison group. Studies were only included if they reported data post-release.Results: N  = 15 studies met the inclusion criteria. We found less opioid use, less other drug use, higher treatment engagement post-release and less re-incarceration among treated individuals compared to the comparison group. Moderator analyses showed some influence of length of follow-up period and study quality.Conclusions: Incarceration-based OST reduces drug use, re-incarceration and leads to higher treatment engagement after release. More research is needed on the effects of incarceration-based OST on secondary outcomes (e.g. health and social integration) and on factors that moderate these effects.